The year of the Tiger : the major run that made Tiger Woods - Miller, Brody (Harper, an imprint of HarperCollinsPublishers, 2025)
"The inside story of legendary golfer Tiger Woods' magnificent run, when he won all four major tournaments in a single calendar year, becoming the greatest player of his generation--a show of unparalleled dominance in the sport with which he has become synonymous. In the annals of golf, one achievement towers above all others--the Tiger Slam. A quarter century ago, between 2000 and 2001, Tiger Woods accomplished a feat so extraordinary, it may never be replicated. Published in time for the twenty-fifth anniversary of this remarkable event, The Year of the Tiger transports readers back in time to witness the sheer brilliance and unrelenting determination that propelled Woods to the pinnacle of his game. Through vivid storytelling, meticulous research, and fresh interviews, The Year of the Tiger uncovers new details about the four major championship victories that cemented Tiger's status as an all-time great--while also exposing the cracks in his superstardom that led to his inevitable downfall." --